Life satisfaction index and physical sustainability aspects of kampung settlement in Malang, Indonesia - ., surjono; M, Ridhoni (International Journal of Engineering and Technology, 2019)
Kampungs, common places in Indonesia-Malaysia-Singapore -Brunei, are widely considered as slump areas. In Indonesia, kampungs are urban settlements that cover large part of urban areas [1]. Therefore, as a part of efforts to achieve Sustainable Development Goals (SDGs), it is significant to develop and improve the living environment of urban kampung based on sustainable development criteria. Many efforts to upgrade urban kampung should result in increasing life satisfaction on the inhabitants. This paper investigate the link between physical aspects and life satisfaction in urban kampungs, using the case in Malang City, Indonesia. This research focused on social-economic aspects of sustainable development. Selected social-economic aspects of life satisfaction were assessed and were aggregated into life satisfaction index based on the formula used by the National Central Body of Statistic and the physical sustainability of kampung was measured into an aggregate index using fuzzy logic approach. The research found that the most significant aspect which contributed to life satisfaction was the harmony within the family, while the lowest scores were related to income and occupation. The outputs also prove that life satisfaction of the community correlates with sustainability aspects of kampung’s physical entities.